2012
DOI: 10.1007/s00436-012-2824-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro determination of anticryptosporidial activity of phytogenic extracts and compounds

Abstract: Cryptosporidiosis caused by Cryptosporidium spp. is an important diarrhoeal disease observed in farm animals and humans, especially in young or immunocompromised individuals. A novel cell culture assay for testing extracts and pure compounds against Cryptosporidium parvum in 96-well microplate format was established and evaluated. It is based on previously described indirect fluorescent antibody techniques and was optimised for higher sample throughput. Rapid assessment of minimal inhibitory concentrations (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…Phytochemicals possess a wide range of chemical structures, and in experimental studies, different phytocompounds have also shown an array of biological activities, which have often been found to vary from compound to compound (Newman and Cragg 2007;Teichmann et al 2012;Wink 2012). This may explain, in part, as to why, in the present study, different tested phytochemicals revealed different levels of anthelmintic activity.…”
Section: Resultssupporting
confidence: 39%
See 2 more Smart Citations
“…Phytochemicals possess a wide range of chemical structures, and in experimental studies, different phytocompounds have also shown an array of biological activities, which have often been found to vary from compound to compound (Newman and Cragg 2007;Teichmann et al 2012;Wink 2012). This may explain, in part, as to why, in the present study, different tested phytochemicals revealed different levels of anthelmintic activity.…”
Section: Resultssupporting
confidence: 39%
“…Although, there are many evidences of the antiparasitic effects of these phytoconstituents, however, their purported antiparasitic effects have also been the cause of controversy amongst the scientific community (Athanasiadou and Kyriazakis 2004). A perusal of literature reveals that majority of scientific evidences supporting the antiparasitic properties of phytoconstituents have come from in vitro studies (Athanasiadou and Kyriazakis 2004;Nagajyothi et al 2012;Teichmann et al 2012;Zahir et al 2012), because employing this method the phytoconstituents can be reliably quantified without the interference of other plant components or nutrients. Therefore, in this study we employed a suitable in vitro assay to test the anthelmintic efficacy of four selected phytochemicals on H. diminuta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…parvum both in vitro and in vivo [177][178][179][180][181][182][183][184][185][186], among which maduramicin and monensin (Figure 1) were identified as the most active ones [177][178][179][180][183][184][185][186]. µM without any adverse effects to the host cells [178].…”
Section: Cryptosporidiosismentioning
confidence: 99%
“…Plants present a rich source of bioactive compounds and have a long history of use for prevention and treatment of various human and animal illnesses, including parasitic diseases [ 1 , 20 , 29 , 31 ]. For example, the isoflavone genistein from soybean, the flavonolignan mix silymarin (with silibinin as a main compound) from the milk thistle [ 22 , 39 , 43 ] or the ferulic acid-derived curcuminoid curcumin from turmeric [ 34 ] have been found to possess anti-cryptosporidial activity in vitro . The xanthone mangiferin (known from mango) has demonstrated some efficacy in vivo [ 30 ].…”
Section: Introductionmentioning
confidence: 99%